SUSTAINABLE STRATEGY FOR A MORE RESILIENT STATE BORDER GUARD ORGANIZATION - Jukšs, Valdis; Iliško, Dzintra; Badjanova, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In line with the EU2020 strategy, sustainable development has been a high priority in the EU. Implementing a sustainable strategy in any organization is a complex, value-based multi-dimensional process where sustainability is translated and adapted in the regional context. Implementation of a sustainability strategy requires defining a vision, developing sustainable strategies, assessing the current state of arts, monitoring the process and providing the platform for all actors involved to implement the vision.The aim of the article is to offer a conceptual basis for building a sustainable strategy in the state border guard organization. This involves rethinking, repositioning the current strategy and formulating a future-oriented perspective in order to enhance awareness of the complexity, accept the dynamic nature of corporate sustainability and to adopt a proactive behavior towards sustainability issues. The paper presents a case study on challenges that the State Border Guard organization is facing for implementing a sustainability strategy. The research study presents a qualitative study for a deeper understanding of the process of conceptualizing and implementing a sustainability strategy in Latgale region. The methodology employed in the study is semi-structured interviews with the representatives of administration on the process and the challenges of implementing sustainability strategy.